Radar Study of the Bay of Bengal cyclone of 19 November 1977 - RAGHAVAN, S.; RENGARAJAN, S.; VARADARAJAN, V. M. (MAUSAM, 1980)
The severe cyclone which hit the Andhra Pradesh cost on 19 November 1977 was observed by the Cyclone Warning Radar at Madras for about 72 hours. The large range of detectability, the larger radar echo area, tight banding, double eyewall and the high rate of rainfall in the eyewall region all indicate that the storm had an unusually severe intensity on the 17 and 18 of November. There was, however, a general decrease in the total echo area, total areal rainfall, maximum eyewall rainfall rate and maximum cloud top heights in the eyewall from the 18th to the 19th. It is inferred that the storm might have weakened to some extent while still at sea. The eye maintained a nearly constant diameter of 60 km until the storm came close to coast when the eyewall broke up. The storm probably reorganised later with a smaller eye but this could not be observed by radar. The storm motion during the period of radar observation was northwestwards. Precyclone squall line orientation and extrapolation of radar track were found to be good predictors of storm motion but other radar features were not.